Iatrogenic Femoral Arteriovenous Fistula with Pseudoaneurysm Associated with Worsening Heart Failure Years after Percutaneous Impella Placement - Andy Y. Wang; Ali Al Jabri; Edward R. Jewell; Angela L. Jellison (Case Reports in Vascular Medicine)
Iatrogenic arteriovenous fistulas (AVFs) and pseudoaneurysms (PSAs) are rare complications that may develop years after vascular access, and high-volume flow through these AVFs have been hypothesized to contribute to chronic heart failure. Formation of an AVF or PSA following Impella placement has rarely been described in the literature. Here, we describe a patient who had percutaneous placement of an Impella ventricular assist device through his right groin three years prior, now presenting with worsening heart failure and symptoms of volume overload. He was discovered to have a new, high-flow common femoral artery to femoral vein AVF with an associated PSA. The AVF and associated PSA were resected and repaired. This case study highlights a rare access-site complication from percutaneous Impella placement associated with worsening heart failure, strategies for preventing this complication during peripheral access, and the need to consider this differential in such a patient with a history of peripheral access who has an unexplained worsening of heart failure.